The Competition between Relationship-Based Microfinance and Transaction Lending - Jan Schrader (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
We empirically analyze the competition between a relationship lender and a transaction lender in the credit business with micro and small entrepreneurs. Drawing on a data set about the customers of the relationship lender ProCredit Ecuador combined with data about all other loans of these customers in the Ecuadorian banking system, we are able to analyze the competition between different banking types. We find that the quality of ProCredit borrowers who have a trans- action loan as well is below average. They also have higher default probabilities. Furthermore, we find evidence that ProCredit customers with payment problems prefer to serve their relationship loan while defaulting on their transaction loan. These findings suggest that customers of a relationship bank value their banking relationship and try to protect it as long as possible. This result stands in contrast to the common presumption that the market entrance of transaction lenders will destroy the market for lenders applying relationship lending techniques.
Keywords: O16; D14; G21; 330; Microfinance; Competition; Relationship Lending; Transaction Lending